Delayed hepcidin response explains the lag period in iron absorption following a stimulus to increase erythropoiesis. Issue 10 (10th September 2004) - Frazer, D M; Inglis, H R; Wilkins, S J; Millard, K N; Steele, T M; McLaren, G D; McKie, A T; Vulpe, C D; Anderson, G J
Abstract : Introduction: The delay of several days between an erythropoietic stimulus and the subsequent increase in intestinal iron absorption is commonly believed to represent the time required for body signals to programme the immature crypt enterocytes and for these cells to migrate to the villus. Recent data however suggest that signals from the body to alter absorption are mediated by circulating hepcidin and that this peptide exerts its effect on mature villus enterocytes. Methods: We have examined the delay in the absorptive response following stimulated erythropoiesis using phenylhydrazine induced haemolysis and correlated this with expression of hepcidin in the liver and iron transporters in the duodenum. Results: There was a delay of four days following haemolysis before a significant increase in iron absorption was observed. Hepatic hepcidin expression did not decrease until day 3, reaching almost undetectable levels by days 4 and 5. This coincided with the increase in duodenal expression of divalent metal transporter 1, duodenal cytochrome b, and Ireg1. Conclusion: These results suggest that the delayed increase in iron absorption following stimulated erythropoiesis is attributable to a lag in the hepcidin response rather than crypt programming, and are consistent with a direct effect of the hepcidin pathway on mature villus enterocytes.